Immunochromatography Test Kit for Detection of Dexamethazone and Prednisolone in Herbal Medicinal Products - Matapatara, Waliluk; Likitthanaset, Masvalai (Journal of Health Science of Thailand, 2017)
The adulteration of dexamethasone and prednisolone in herbal medicinal products claims serious side effects and leads to premature mortality. Therefore, a qualitative immunochromatographic test kit for screening the adulterated dexamethasone and prednisolone in herbal medicinal products was developed. This test kit was found to be rapid and easy to perform with no pre requisite regarding laboratory equipments or skills. The detection is accomplished by the reaction between anti-dexamethasone gold conjugate and dexamethasone and/or prednisolone indicated by a purplered color band on a nitrocellulose membrane. The sensitivity for detection of dexamethasone and prednisolone in terms of the cut-off concentrations was determined to be 1 and 50 μg/ml, respectively. The accuracy of this test kit was comparable with that of thin layer chromatographic technique. It was therefore concluded that the application of immunochromatography test kit for detection of dexamethasone and prednisolone in herbal medicinal products would be fruitful for surveillance in public health consumer protection. The knowledge of this rapid test would possibly be further useful for the development of various medicinal product testings.